KEDUDUKAN ANAK DI LUAR NIKAH DI INDONESIA - Hamiyuddin, Hamiyuddin (Musawa: Journal for Gender Studies, 2018)
Children are the mandate and gift of Allah SWT, which we must always guard because in him the inherent dignity, dignity and rights as human beings must be upheld. Out-of-wedlock children are children born to a woman, while the woman is not in a legal marriage with a man who intercourse with her. This paper discusses the legal position of extramarital children in Indonesia with the aim of knowing the criteria for extramarital children according to Islamic law and the position of out-of-wedlock children in religious courts in Indonesia based on Law No. 1 of 1974 concerning marriage.